2019
DOI: 10.7150/ijbs.34076
|View full text |Cite
|
Sign up to set email alerts
|

TFAP2A Induced KRT16 as an Oncogene in Lung Adenocarcinoma via EMT

Abstract: Objectives : keratin 16 (KRT16) is a type I cytokeratin that overexpressed in many kinds of cancers, but unlike other keratins, KRT16 was poorly studied, so the aim of current study was to determine the biological role of KRT16 in lung adenocarcinoma (LUAD). Materials and Methods : by utilizing open access data, we determined KRT16 expression in LUAD. After that we evaluated the biological role of KRT16 in-vitro and in-vivo . We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 20 publications
6
47
0
Order By: Relevance
“…But the mechanism for the increased ITPKA expression is complex and could be regulated by several molecular mechanisms including DNA methylation, microRNA, or aberrant transcription factor signaling. In the previous study from our lab, Liu et al determined that the transcription factor TFAP2A promotes tumor metastasis and EMT via activating cytokeratin KRT16 transcriptionally [8], in the current study we identified TFAP2A could also activate the expression of ITPKA, which is a new mechanism for the ITPKA hyper-expression in lung adenocarcinoma.…”
Section: Introductionsupporting
confidence: 61%
See 4 more Smart Citations
“…But the mechanism for the increased ITPKA expression is complex and could be regulated by several molecular mechanisms including DNA methylation, microRNA, or aberrant transcription factor signaling. In the previous study from our lab, Liu et al determined that the transcription factor TFAP2A promotes tumor metastasis and EMT via activating cytokeratin KRT16 transcriptionally [8], in the current study we identified TFAP2A could also activate the expression of ITPKA, which is a new mechanism for the ITPKA hyper-expression in lung adenocarcinoma.…”
Section: Introductionsupporting
confidence: 61%
“…Because we already reported TFAP2A is also significantly hyper-expressed in LUAD [8]. We came to the conclusion that TFAP2A should be an important TF for ITPKA and contribute to the ITPKA hyper expression in LUAD.…”
Section: Tfap2a Is the Upstream Transcription Factor For Itpka And Itmentioning
confidence: 77%
See 3 more Smart Citations